HOBACGEN: Database System for Comparative Genomics in Bacteria - Perrière, Guy; Duret, Laurent; Gouy, Manolo (Genome Research, 2000)
We present here HOBACGEN, a database system devoted to comparative genomics in bacteria. HOBACGEN contains all available protein genes from bacteria, archaea, and yeast, taken from SWISS-PROT/TrEMBL and classified into families. It also includes multiple alignments and phylogenetic trees built from these families. The database is organized under a client/server architecture with a client written in Java, which may run on any platform. This client integrates a graphical interface allowing users to select families according to various criteria and notably to select homologs common to a given set of taxa. This interface also allows users to visualize multiple alignments and trees associated to families. In tree displays, protein gene names are colored according to the taxonomy of the corresponding organisms. Users may access all information associated to sequences and multiple alignments by clicking on genes. This graphic tool thus gives a rapid and simple access to all data required to interpret homology relationships between genes and distinguish orthologs from paralogs. Instructions for installation of the client or the server are available at http://pbil.univ-lyon1.fr/databases/hobacgen.html.